Studies of 137Cs absorption-desorption processes in sediments, using γ-ray spectroscopy - Mertzimekis, T. J.; Ioannides, K. G.; Papachristodoulou, C. A.; Stamoulis, K. C.; Karamanis, D. T. (HNPS Advances in Nuclear Physics, 2020)
The description of 137Cs behavior during water to sediment transport generally involves the characterization of the sorption process in a particular hydro-geological system by certain prescribed kinetics parameters, hi the present work the kinetics of radiocesium sorption and desorption and the corresponding radiocesium distribution profiles in lake sediment cores were investigated. Radiocesium reaches rapidly (< than 5 d) at a depth which does not exceed 4 cm. The desorption of radiocesium was found to depend upon cation concentrations. Empirical laws were derived both for cesium adsorption and desorption.